The Future Challenge: Water Demand Forecasting - Anggi Nidya Sari (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Penerbangan Palembang, 2021)
Palembang has abundant water sources; the city of Palembang is traversed by one of the longest rivers in Indonesia, the Musi River. However, population growth is increasing over time, as is the need for clean water. Projections of the amount of clean water demand in the future are needed; apart from anticipating water shortages, water demand projections are required to construct clean water facilities and infrastructure. This research was conducted using statistical calculations to calculate the population in the next ten years. The population of Palembang in 2030 is projected to increase to1,898,221 inhabitants. The results of this population projection are used in calculating the total water demand in 2030. The total water demand is obtained from the calculation of domestic, non-domestic, fire hydrant, and water loss needs. In 2030, the total amount of water needed is 6,816 L / second.